The impacts of capital structure towards Government-Linked Companies & Non-Government Linked Companies: evidence from Malaysia / Husna Amira Ismail - Ismail, Husna Amira (2017)
This study examines the impacts of capital structure towards Government-Linked Companies (GLCs) and Non-Government Linked Companies (NGLCs) in Malaysia. This study considers the data from 2009-2016 (eight years period) and comprises of 20 GLCs and 20 NGLCs in Malaysia. Debt ratio is perceived as the relevant factor as one of the dependent variables. Meanwhile, profitability, tangibility, liquidity and firm size as the independent variables. The findings of this study for GLCs showed that there are positive relationship between the tangibility and firm size towards the debt ratio. Whereas, profitability and liquidity showed are negative relationship towards debt ratio. For the NGLCs, showed that there are positive relationships between the firm size only. Meanwhile, another three variables are in negative relationships.